Pendampingan Tes Ability: Tes Keterampilan dan Kemampuan Kognitif - Nova, Andi; Tantri, Afri; Desy M, Ruhama; Afrial M, Beny (Jurnal Pengabdian Keolahragaan dan Sains, 2025)
Supporting graduate competencies requires several skills that can support students' abilities. One of the activities that can support competence that becomes experience is mentoring, training and workshop activities. The implementation of this activity was carried out by the PAR (Participatory Action Research) mentoring method.The mentoring activity carried out is the Ability Test which aims to improve students' ability to understand and implement the Ability test according to test norms. The activity was carried out for two days at the multipurpose building of Universitas Samudra with 30 participants from FKIP UNSAM Physical Education Students. The results of the individual ability test showed that 13 participants (43.3%) obtained the Very Good category, 14 participants (46.7%) in the Good category, and 3 participants (10%) in the Adequate category. These results show that in theory and practice Physical Education Students are able to conduct tests and implement ability tests in schools as a provision for PLP and prospective teachers who have competence.